(untitled) (Observatorio Económico, 2009)
As in poorly anticipated disasters, financial crises go out in search of culprits. The list is a familiar one: badly incentivized regulators, lax central banks, overhyped economists and credit rating agencies, and overpaid bankers. Some, such as Will Hutton, the former editor of the British newspaper The Observer, add journalists to it. Continue reading...